Job Creation through Infrastructure Investment in the Middle East and North Africa - Ianchovichina, Elena (World Bank, Washington, DC, 2012)
In the next 10 years or so, the infrastructure sector has the potential to generate significant employment. This paper estimates annual job creation of about 2.0 million in direct jobs and 2.5 million in direct, indirect and induced infrastructure-related jobs just by meeting the infrastructure investment needs of about 6.9 percent of gross domestic product (about US$106 billion) for the Middle East and North Africa region on average. The breakdown in expected needs is 11 percent in developing oil exporters, 6 percent in oil importing countries, and 5 percent in the Gulf Cooperation Council oil exporters. Needs are particularly high in electricity and roads. While important, infrastructure job creation will not resolve the region's unemployment problem alone and its job creation potential varies greatly across countries. Moreover, the current ability to finance and hence meet the infrastructure needs varies significantly across countries. Oil importers are likely to fall short under business as usual scenarios. In a region in which the public sector is the main source of infrastructure financing, fiscal choices will thus matter to job creation through infrastructure. But there are more challenges, including the governance of job creation, and the proper targeting and costing of subsidies for job creation and the (re)training programs needed. Managing expectations will also matter, as infrastructure jobs will help but will not solve the region's unemployment and underemployment problems.